Establecimiento in vitro de musáceas (AA, AAA, AAB) vía organogénesis directa - Mora Mackensen, Miguel Antonio (2017)
VIII. SUMMARY This research was carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at km 7 1/2 of the Babahoyo - Montalvo road. It consisted of the in vitro establishment of musaceae (AA, AAA, AAB) via direct organogenesis. The objectives of this study were: To establish in vitro 11 accessions of musa from AA, AAA, and AAB genomes and to evaluate the establishment of the explants in two induction protocols. During the development of this research, the due process consisted in collecting, disinfecting and establishing in vitro eleven accessions of musaceae of different species in two induction protocols. The agronomical variables evaluated were: Contamination of explants, Phenolization of explants, and establishment of explants. A Completely Random Design (DCA) was used with uneven number of repetitions. The variables were analyzed using non-parametric statistics using the Kruskal-Wallis test, applying the statistical software InfoStat. The results showed that the treatment 2 excelled compared to treatment 1, because it presented a more optimal protocol for the in vitro establishment of musaceae, obtaining 100% of explants free of contamination. In conclusion, treatment 2 had the lowest percentages of contamination (0%), phenolization (10%) and the highest percentage of establishment of the explants (90%).